DIVERSITY OF THE UNIONID FRESHWATER MUSSELS (BIVALVIA: UNIONIDAE) IN BRANTAS RIVER, EAST JAVA, INDONESIA - Moch. Affandi; Leonard Ady Candra; Astra Budi Priatama; Bambang Irawan; Agoes Soegianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
The aims of this study are to provide data and information about diversity, dominance, and distribution of the Unionidae mussels species in Brantas River, East Java, Indonesia. Mussel samples were collected from 14 sampling stations along the Brantas River, starting from upstream in Tulungagung to downstream in Surabaya (± 170 km) in April-May 2012. The results showed that five species of mussels, namely: Contradens contradens, Elongaria orientalis, Rectidens sumatrensis, Pseudodon vondembuschianus and Pilsbryoconcha exilis were observed in the Brantas River. Contradens contradens was the “dominant” species, followed by Elongaria orientalis as a “common” species, and Rectidens sumatrensis, Pseudodon vondembuschianus and Pilsbryoconcha exilis as “rare” species. Distribution of each species in the Brantas River tends to be concentrated in downstream of the river, mainly located in station 13. According to the IUCN Red List, Rectidens sumatrensis was categorized in “Data Deficient”, while Pseudodon vondembuschianus and Pilsbryoconcha exilis were categorized in “Least Concern”.